Bathtime - Sirett, Dawn; Harvey, Victoria (London Dorling Kindersley, 2009)
Help your baby discover all about bathtime with touch and feel textures. Stroke, tickle and touch the textures together with your baby and help them discover all about bathtime. Let their little hands roam and feel how shiny the bath ducks are and how soft the fleecy towels feel. They'll learn as you play
Picture books
27
Keywords: Baths -- Children's picture books; Baths